HAK UPAH DAN THR PEKERJA SELAMA PEMUTUSAN HUBUNGAN KERJA (STUDI KASUS : PUTUSAN PENGADILAN NEGERI BANDUNG KELAS 1 A KHUSUS NOMOR 9/PDT.SUS-PHI/2018/PN BDG) - Ragil Aryo Pandito; Gunardi Gunardi (Fakultas Hukum Universitas Tarumanagara, 2022)
The problem that very often exists between a worker/worker and an entrepreneur is the impact of Termination ofEmployment, labor for a work relationship will soon be terminated due to the complexity of a problem from endingthe livelihood of a worker or worker. Termination of Employment Relations has legal consequences for bothemployers and workers/labor. The rights and obligations of each party must be fulfilled until there is a decision fromthe Industrial Relations Court, in which workers will receive legal protection, namely receiving severance pay orservice pay as a substitute for termination of employment. Sulissetiyani P.W as Plaintif one has a position as ananalyst who has worked for 5 years and Warsiyo as plaintif two has a position as an Implementing Assistant whohas worked for 5 years and will be dismissed because Bahar Dinur Islam is often late for work without being given afair severance pay in accordance with the Act. Invite so that Sulissetiyani P.W and Warsiyo propose. The BandungDistrict Court at the Industrial Relations Court filed a lawsuit, but the rights for workers in the decision to bringseverance pay or better known as gratuities during the period of service have not been fulfilled. normative of aresearch is used with literature study techniques in data collection. just like the meaning of a symbol of justice and asymbol of scales, a judge should make considerations in order to achieve maximization of workers who have rightsthat should be fulfilled.